Effect of verticalization with Erigo® in the acute rehabilitation of severe acquired brain injury - Ancona, Emilio; Quarenghi, Annamaria; Simonini, Marcello; Saggini, Raoul; Mazzoleni, Stefano; De Tanti, Antonio; Saviola, Donatella; Salvi, Giovanni Pietro (Neurological sciences, 2019)
The recovery of the orthostatism after a severe acquired brain injury (sABI) is an essential objective to pursue in order to avoid the occurrence of secondary complications resulting from prolonged immobilization to which the patient is subjected during the acute phase. This randomized controlled trial aims to evaluate the effect of verticalization with the lower limb robot-assisted training system Erigo® versus conventional neurorehabilitation in 44 adult subjects affected by sequelae of sABI in the acute rehabilitation phase, related to cardiorespiratory signs and measures of impairment and activity. At the end of the study (20 treatment sessions, 5 sessions per week), in both groups of patients, there were no dropouts nor adverse events. In subject verticalized with Erigo ®, there were no episodes of (pre)syncope from orthostatic hypotension nor postural orthostatic tachycardia and cardiorespiratory signs remained stable; moreover, there were no increase in muscle tone nor reduction in range of motion at lower limbs. Results obtained show improved outcomes on the whole and in a similar way in both groups; however, the improvement in scores of the National Institutes of Health Stroke Scale, the Tinetti scale, and the Functional Independence Measure from the enrollment to the end of the treatment cycle being equal, the evaluation performed at the 10th session allows to establish that the improvement appears earlier in the intervention group and later in the control group. The more rapid recovery of impairments and some activities in subjects treated with Erigo ® could allow a “time-saver” to devote to the rehabilitation of sensory-motor functions which are more complex and subordinated to the preliminary reacquisition of elementary postures and motor strategies.